2023
DOI: 10.4314/ahs.v23i1.78
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of literature on health financing reforms in Uganda – progress, challenges and opportunities for achieving UHC

Abstract: Background: Universal health coverage (UHC) is one of the sustainable development goals (SDG) targets. Progress towards UHC necessitates health financing reforms in many countries. Uganda has had reforms in its health financing, however, there has been no examination of how the reforms align with the principles of financing for UHC. Objective: This review examines how health financing reforms in Uganda align with UHC principles and contribute to ongoing discussions on financing UHC. Methods: We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The implementation of most current UHC programs have suffered significant setbacks stemming from lack of administrative coordination within the respective ministry of health´s overall structures, inadequate health information systems, lack of integrated clinical and frontline health worker data collection and synthesis networks, insufficient utilization and inaccurate interpretation of the available data, underfunding and poor quality medical facilities, thereby lowering the overall success of the programs. Experiences from sub-Saharan countries like Uganda have shown that health financing and risk prevention strategies protecting UHC reforms are far from the desired results [4] .…”
Section: Access To Universal Health Coveragementioning
confidence: 99%
“…The implementation of most current UHC programs have suffered significant setbacks stemming from lack of administrative coordination within the respective ministry of health´s overall structures, inadequate health information systems, lack of integrated clinical and frontline health worker data collection and synthesis networks, insufficient utilization and inaccurate interpretation of the available data, underfunding and poor quality medical facilities, thereby lowering the overall success of the programs. Experiences from sub-Saharan countries like Uganda have shown that health financing and risk prevention strategies protecting UHC reforms are far from the desired results [4] .…”
Section: Access To Universal Health Coveragementioning
confidence: 99%